THE EFFECT OF SHARIAH PRODUCTS AND PERCEPTION OF QUALITY OF SERVICES ON CUSTOMER SATISFACTION IN SHARIA BANKS PONOROGO - Rehardian Pujo Satrio; Dhika Amalia Kurniawan (University of Darussalam Gontor, 2018)
The purpose of this study is to analyze the effect of shariah products and perception of quality of services on customer satisfaction in BRI sharia banks ponorogo. Type of this research is quantitative with the technique of purposive sampling. The population in the study is customer who have felt service in BRI shariah bank Ponorogo with the total sample 60 respondents. The data obtained through the respondents by using data collection tools in the form of question form/questionnaire which measured using the Likert scale. Data analysis techniques is multiple linear regression test. The results of this study indicate that tangiable, responsive and shariah products affect customer satisfaction, while reliability, assurance, empathy have no effect on customer satisfaction. As follows (1) BRI Shariah bank Ponorogo should enhance the factors that influence positive toward customer satisfaction such to improve service quality(2) evaluating and enhancing the factors which do not affect positive toward customer satisfaction such as giving accurate information, fast service, patient service and not to see social status, so that it can create customer satisfaction by providing maximum service.